Prevalence of coronary artery anomalies in young sudden cardiac death: insights from a prospective state-wide registry. (3rd October 2022) - Paratz, E; Van Heusden, A; Zentner, D; Morgan, N; Smith, K; Ball, J; Thompson, T; James, P; Connell, V; Pflaumer, A; Semsarian, C; Ingles, J; et al.
Abstract: Background: Coronary artery anomalies (CAAs) have been previously implicated as a major cause of young sudden cardiac death (SCD), particularly in exercise-related SCD with a reported prevalence of up to 33%. Methods: A state-wide prospective out-of-hospital cardiac arrest registry identified all patients aged 1–50 years who experienced an SCD and underwent autopsy from April 2019 to April 2021. Rates of normal anatomy, normal variants and CAAs were identified and circumstances and cause of death for patients with CAAs examined. Results: Of 1, 477 patients who experienced cardiac arrest during the study period, 490 underwent autopsy and were confirmed to have experienced SCD. Of these 490 patients, five (1.0%) had a CAA identified with three having anomalies of coronary origin and two having anomalies of coronary course. In no cases was the CAA deemed responsible for the SCD. In two cases, severe coronary disease and intra-coronary thrombus with histological evidence of acute myocardial infarction were identified, in the third critical coronary disease was found, the fourth had an unrelated thoracic aortic dissection and the fifth had cardiomegaly in the setting of illicit drug use. Of 27 patients who experienced their SCD during exercise, only one had a CAA identified (the patient with thoracic aortic dissection). Conclusion: In this prospective cohort of consecutive young patients with SCD who underwent autopsy, CAAs occurred in 1.0% of patients and did not cause any deaths. The role of CAAs in causing young SCD appears to be less significant than previously hypothesised. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): NHMRC, NHF